2017
DOI: 10.1016/j.fm.2017.04.019
|View full text |Cite
|
Sign up to set email alerts
|

Influence of soy fortification on microbial diversity during cassava fermentation and subsequent physicochemical characteristics of garri

Abstract: 23This study investigated the influence of the addition of soy products on the microbiology, 24 nutritional and physico-chemical characteristics of garri, a fermented cassava product.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…3). Previous studies indicate that lactic acid bacteria from the Lactobacillus, Weissella and Leuconostoc genera 16,17 together with the genus Bacillus 5,18 were highly abundant in fermented cassava. However, the high abundance of Zymomonas observed in the latter sample was not reported in other studies.…”
Section: Resultsmentioning
confidence: 97%
“…3). Previous studies indicate that lactic acid bacteria from the Lactobacillus, Weissella and Leuconostoc genera 16,17 together with the genus Bacillus 5,18 were highly abundant in fermented cassava. However, the high abundance of Zymomonas observed in the latter sample was not reported in other studies.…”
Section: Resultsmentioning
confidence: 97%
“…Adding an ingredient might make the gari less sour by dilution effect, and/or by buffering effect, mainly caused by soy proteins that slows down the pH drop, resulting in higher pH. Higher pH values were also reported for gari fortified with 13% soybean flour (4.96 compared to 4.79 for the control; Ahaotu et al, ), while a slight decrease in pH was found between unfortified and 10%‐soy–gari after 24 hr and 48 hr of fermentation (Afoakwa et al, ).…”
Section: Resultsmentioning
confidence: 98%
“…Higher pH values were also reported for gari fortified with 13% soybean flour (4.96 compared to 4.79 for the control; Ahaotu et al, 2017), while a slight decrease in pH was found between unfortified and 10%-soy-gari after 24 hr and 48 hr of fermentation (Afoakwa et al, 2010).…”
Section: Ufsa a Similar Range Was Found In 14 Samples Collected In mentioning
confidence: 85%
“…Soy ingredients have unique flavors, which if added in high quantity, can unduly influence the final flavor profile of the recipe, resulting in changes in consumer compliance. Some authors use soy flour to enhance the nutritional value of different foods, reporting exchanges ranging from 5% to 40% to make specific recipes such as bread, 14 tortillas, 15 biscuits, 16 fritters, 17 garri, 18 and soup. 19 In any of these publications, exchange of soy flour for other main ingredients in less than 10% of weight did not modify the acceptability of the food.…”
Section: Research Aim 3 Proposes That Soy Can Serve As a Cost-effectimentioning
confidence: 99%